2007
DOI: 10.1111/j.1399-3054.2006.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Frankia genotypes occupying Alnus nepalensis nodules with respect to altitude and soil characteristics in the Sikkim Himalayas

Abstract: doi: 10.1111/j.1399-3054.2006.00872.x We investigated the distribution of Frankia genotypes with respect to three altitudinal zones in the Sikkim Himalayas. The study was carried out for 90 Alnus nepalensis trees at nine different locations from three altitudes from the east and north districts of Sikkim, India. We used a PCR-based technique to amplify the internally transcribed spacer (ITS) region of the rrn operon using two primers specific for the distal part of 16S ribosomal RNA (rRNA), ITS and proximal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…This diversity was confi rmed by the nucleotide sequencing. In a similar study we found two different ARPs for ten Alnus nepalensis root nodule samples collected from North Sikkim [14]. This is indicative of a larger diversity for Frankia nodulating Hippophae salicifolia compared to that nodulating alder.…”
Section: Nucleotide Sequencing and Analysismentioning
confidence: 52%
See 3 more Smart Citations
“…This diversity was confi rmed by the nucleotide sequencing. In a similar study we found two different ARPs for ten Alnus nepalensis root nodule samples collected from North Sikkim [14]. This is indicative of a larger diversity for Frankia nodulating Hippophae salicifolia compared to that nodulating alder.…”
Section: Nucleotide Sequencing and Analysismentioning
confidence: 52%
“…The gel was then scanned and photographed using BioRad GelDoc1000 and the profi les were analyzed using the Multi Analyst ® software. These patterns were compared with patterns of similar digestion carried out on alder compatible Frankia [14]. NT-SYS (version 2.1) was used for cluster analysis of the banding patterns.…”
Section: Amplicon Restriction Pattern (Arp) Analysis Of Pcr Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a threshold of 5%, all Frankia populations in nodules of A. oblongifolia were placed in one group, suggesting no differentiation by mountaintop and a limited overall level of diversity, with one cluster present, compared to the potential presence of at least six clusters of frankiae within the Alnus host infection group described in previous studies (34,49). Low overall diversity has also been described to occur in other studies of natural Frankia diversity in root nodules of various alder species (11,23,27,29).…”
mentioning
confidence: 82%